La ciudad oculta, Alcalá de Henares 1753-1868 : el nacimiento de la ciudad burguesa / Luis Enrique Otero Carvajal, Pablo Carmona Pascual, Gutmaro Gómez Bravo - Carmona Pascual, PabloGómez Bravo, Gutmaro; Otero Carvajal, Luis Enrique (Alcalá ensayo ; 21)
Bibliografía: p. 867-880